Mechanisms of antiviral immunity induced by a vaccinia virus recombinant expressing herpes simplex virus type 1 glycoprotein D: cytotoxic T cells. - Martin, S (1987)
We used a transfected L cell and a vaccinia vector carrying the herpes simplex virus type 1 (HSV-1) gene coding for glycoprotein D (gD) to characterize HSV-specific T-cell responses. Various studies with mice revealed that the vectors could stimulate some HSV-specific T-cell responses. Although the majority of the T cells contributing to the HSV-1 gD-specific proliferative response were of the Lyt-2.1+ phenotype, cytotoxic T cells (Tc), surprisingly, were not induced by these gD vectors. Even though gD appeared to be a target for a class II major histocompatibility complex (MHC)-restricted killer cell, neither gD vector was capable of forming a target cell complex which could be recognized by class I MHC-restricted HSV-specific Tc. Further investigation of the gD-specific responses revealed the presence of potent suppressor cells and factors capable of inhibiting HSV-specific Tc induction in in vitro assays. One interpretation of these data is that class I MHC-restricted HSV- and gD-specific Tc do not develop during HSV infection because of active suppression.